Site directed mutagenesis of insulin-degrading enzyme allows singling out the molecular basis of peptidase versus E1-like activity: the role of metal ions. Issue 2 (10th January 2019) - Bellia, Francesco; Lanza, Valeria; Ahmed, Ikhlas Mohamed Mohamud; Garcia-Vinuales, Sara; Veiss, Eva; Arizzi, Mariaconcetta; Calcagno, Damiano; Milardi, Danilo; Grasso, Giuseppe
Abstract : Four specifically designed IDE mutants have been used to unveil the molecular basis of peptidase versus E1-like activity of the enzyme. Abstract : Four specifically designed IDE mutants have been used to unveil the molecular basis of peptidase versus E1-like activity of the enzyme. We have found that physiological concentrations of copper(ii ) ions inhibit the proteolytic activity of the enzyme towards small and large substrates but have no effect on the E1-like activity of the enzyme.